Palaeoglaciation of Bayan Har Shan, northeastern Tibetan Plateau: glacial geology indicates maximum extents limited to ice cap and ice field scales - Heyman, Jakob; Stroeven, Arjen P.; Alexanderson, Helena; Hattestrand, Clas; Harbor, Jon; Li, Yingkui; Caffee, Marc W.; Zhou, Liping; Veres, Daniel; Liu, Feng; Machiedo, Martin (Journal of Quaternary Science, 2009)
Key locations within an extensive area of the northeastern Tibetan Plateau, centred on Bayan Har Shan, have been mapped to distinguish glacial from non-glacial deposits. Prior work suggests palaeo-glaciers ranging from valley glaciers and local ice caps in the highest mountains to a regional or even plateau-scale ice sheet. New field data show that glacial deposits are abundant in high mountain areas in association with large-scale glacial landforms. in addition, glacial deposits are present in several locations outside areas with distinct glacial erosional landforms, indicating that the most extensive palaeo-glaciers had little geomorphological impact on the landscape towards their margins. The glacial geological record does indicate extensive maximum glaciation, with local ice caps covering entire elevated mountain areas. However, absence of glacial traces in intervening lower-lying plateau areas suggests that local ice caps did not merge to form a regional ice sheet on the northeastern Tibetan Plateau around Bayan Har Shan. No evidence exists for past ice sheet glaciation. Copyright (C) 2009 John Wiley & Sons, Ltd. Geosciences, Multidisciplinary Paleontology SCI(E) 9 ARTICLE 7 710-727 24